AN ANALYSIS EGOISM OF KATHY’S CHARACTER IN NEVER LET ME NOVEL GO BY KAZUO ISHIGURO: egoism, character, friendship - Sheintia Prihastuti; Muhammad Ainul Yaqin (Fakultas Sastra Universitas Gresik, 2023)
This study discusses Kazuo Ishiguro's novel never let me go. This study tells the story of Kathy, a nurse who repeats her childhood story during her time at Haislam, making friends with Ruth and Tommy. The research will focus on Kathy as the main role in the novel. Kathy's egoism character in this novel greatly influences the storyline, Haislam and Kathy make the story at the height of the conflict and many things happen in the novel that are closely related to both of them, especially Kathy's egoism character. Therefore, this research will focus on selfishness Kathy. The purpose of this study is to discuss the character of Kathy based on observations on novel stories, in order to obtain accurate and more complete data. This research will also be supported by several theories from experts so that the data obtained becomes more focused and the researcher also reads more than once so that all the data obtained becomes more complete. The results of this research show that the factors that cause break or conflict in friendships are Kathy's egoism. This research can conclude that Kathy's character has a big influence in the storyline. One's egoism can affect friendship. Someone who has a egoism prioritize their own opinions which can lead to conflicts that damage friendships.